Two new species of the cricket genus Eidmanacris and a new combination name for a third species (Orthoptera, Grylloidea, Phalangopsidae) - Mesa, Alejo [UNESP]; Sperber, Carlos F.; Garcia, Paula C. (My University, 1998)
Two new species of the genus Eidmanacris are described (E. bidentata and E. corumbatai) and a new combination name ( E. alboannulata) is assigned for the species Arachnomimus alboannulatus Piza, 1960 (= E. bicornis Mesa & Mello, 1985). Morphological and karyologycal information are provided, and the structure of the genital sclerites is discussed. [KEY WORDS: Orthoptera, Grylloidea, Phalangopsidae, Eidmanacris, cricket, phallic sclerites, chromosomes].